Analysis of Electromyography (EMG) Signal Processing with Filtering Techniques - Oo, Nandar; Aye, Mya Mya; Oo, Thandar; Win, Lei Lei Yin; Tun, Hla; Pradhan, Devasis (The Indonesian Institute of Science and Technology Research, 2024)
The paper presents the Analysis of Electromyography (EMG) Signal Processing with Filtering Techniques. The problem in this study is how to consider the filtering techniques for fundamental EMG signal processing with high-level accuracy. The research method for designing the simulation codes for observing the EMG signal modeling and digital filtering techniques with mathematical approaches from the signals and systems concepts. The results confirm that the outcomes of this study met the performance target for noise removal techniques of EMG signals in real-world applications.